Distribution of 3G signals over fiber - Beato, Daniel L. (2006)
In this work we study the feasibility of UMTS (3G) transmission over Passive Optical Networks (P.O.N.). In order to achieve such objective, it was developed a simulator, so that we could correctly model the system and conclude about its impairments. The simulation results obtained validate this kind of transmission and highlight the associated limitations.